CONFIRMATORY FACTOR ANALYSIS (CFA) OF THE MALAY VERSION OF COUNSELING SELF-EFFICACY AND SELF DEVELOPMENT OF PUBLIC UNIVERSITY’S COUNSELOR TRAINEES’ - Ghazali, Mazila; Mahmud, Mohd Izwan; Amat , Salleh; Bakar, Abu Yazid Abu (International Journal of Psychosocial Rehabilitation, 2020)
Confirmatory factor analysis (CFA) for counseling self-efficacy and self development of the public university’s counselor trainees were done using IBM_AMOS Version 21.0. A total of 208 respondents, who are trained counselors from Bachelor Degree in Counseling, was involved in the research which currently undergoing intership training. The overall validation procedure in known as the Confirmation Factor Analysis (CFA). The CFA approach to the application of structural equation model by using the AMOS software. Based on CFA for counseling self efficacy and self development fitness indexes for each latent construct were fulfilled.